ICOS expression by effector T cells influences the ability of regulatory T cells to inhibit anti-chromatin B cell responses in recipient mice - Hondowicz, Brian D. (2009)
T regulatory cells are critical for the prevention of autoimmunity. Specifically, Treg cells can control anti-chromatin antibody production in vivo, and this correlates with decreased ICOS expression on CD4(+) T helper cells. Here we test the significance of high ICOS expression by T effector cells, firstly in terms of the anti-chromatin B cell response, and secondly on the ability of Treg cells to suppress T cell help. We bred CD4(+) T cell receptor transgenic mice with mice that carry the Roquin(san/san) mutation. The Roquin gene functions to limit ICOS mRNA such that CD4 T cells from mutant mice express elevated ICOS. Using an in vivo model, TS1.Roquin(san/san) Th cells were compared with wild-type TS1 Th cells with regard to their ability to help anti-chromatin B cells in the presence or absence of Treg cells. Both TS1 and TS1.Roquin(san/san) Th cells induced anti-chromatin IgM(a) antibodies, but the TS1.Roquin(san/san) Th cells resulted in the recovery of more class-switched and germinal center B cells. Neither source of Th cells were capable of inducing long-lived autoantibodies. Treg cells completely suppressed anti-chromatin IgM(a) antibody production and reduced anti-chromatin B cell recovery induced by TS1 Th cells. Importantly, this suppression was less effective when TS1.Roquin(san/san) Th cells were used. Thus, high ICOS levels on effector T cells results in autoimmunity by augmenting the autoreactive B cell response and by dampening the effect of Treg cell suppression.